Kecanduan Internet Ditinjau dari Kecerdasan Emosional Remaja di Warung Internet Kelurahan Sekip Medan - Ferry, Ferry; Elvinawanty, Rianda; Manurung, Yulinda S. (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship between emotional intelligence and internet addiction. The hypothesis proposed in research is there any negative correlation between emotional intelligence with internet addiction on teenagers in internet cafÃ© of Kelurahan Sekip Medan, assuming that the higher emotional intelligence, the lower the internet addiction, and vice versa. The subjects of this study were 114 teenagers in internet cafÃ© of Kelurahan Sekip Medan. This research used emotional intelligence and internet addiction scale. Product Moment (Pearson Correlation) was used to analyze the correlation between two variable using SPSS 20 for windows. The results of the data analysis showed that the correlation coefficient was -0,737 with a significance value of 0.000 (p <0.05). It shows there is a negative correlation between emotional intelligence with internet addiction. The results of this study indicate that the contributions made by the variable of internet addiction on personal adjustment was 54,3 percent, while the remaining 45,7 percent was influenced by other factors that were not examined. Baged on these results, it is concluded that the hypothesis, is acceptale, and there is a negative relationship between the emotional intelligence and internet addiction.